A qualitative study of the dementia-care experiences and educational needs of physiotherapists in the Republic of Ireland. Issue Volume 107:Issue (2020) (June 2020) - Foley, Tony; Sheehan, Cormac; Jennings, Aisling A.; O'Sullivan, Trish
Abstract: Objectives: Gait disturbance and impaired balance lead to a greater risk of falls and hip fractures for people with dementia. Physiotherapists play an important role in multidisciplinary dementia care. This study aimed to explore physiotherapists' experiences of dementia care and sought to identify their dementia-specific educational needs. Design: Qualitative design, using focus group interviews. Setting: Primary care and secondary care physiotherapy services in the Republic of Ireland. Participants: Six focus groups with thirty-two physiotherapists, working in community care and hospital settings. Results: Physiotherapists described a significant dementia-related workload. Challenges to care included absence of a formal diagnosis, clinical uncertainty, scarcity of resources, physical working environment and the assessment of rehabilitation potential. Dementia care was enhanced by the involvement of family members and by collaboration with other allied healthcare professionals. Participants expressed a wish to receive further dementia training and clear evidence-based physiotherapy guidelines. Identified areas of educational need included enhanced communication techniques, use and interpretation of cognitive screening tools, sub-typing of dementia, and ethical issues in dementia care. Conclusions: Our findings indicate that physiotherapists remain challenged by complex aspects of dementia care. Tailored dementia training for physiotherapists should be developed, focusing on their educational needs. Delivery of training should incorporate interactive case-based activities and interprofessional education with other allied healthcare professionals.